Quimioterapia experimental com benzonidazol e óleos essenciais em camundongos inoculados com trypanosoma cruzi II e IV - Zanusso Junior, Gerson (2017)
Chagas disease (DC), or American trypanosomiasis, caused by Trypanosoma cruzi, is considered a neglected and globalized disease. The high morbi-mortality presented by the patients occurs due to the inexistence of an effective drug therapy, represented by only two drugs: benzonidazole (BZ) and nifurtimox (NFX). Therefore, the use of essential oils in the research, both in vitro and in vivo, has demonstrated efficacy against T. cruzi, suggesting a valid strategy to find a new trypanocidal substance. In this context, this thesis aimed to evaluate the efficacy of benzonidazole (BZ) and essential oils of lemon grass (Cymbopogon citratus), ginger (Zingiber officinale) and clove (Syzygium aromaticum) in mice experimentally infected by oral route with T. cruzi II and IV and the influence of treatment time with the reference drug on murine infection by T. cruzi IV. The article 1 evaluated the efficacy of essential oils of C. citratus, Z. officinale and S. aromaticum in mice infected with T. cruzi Y strain. Fresh blood examination (FBE), hemoculture (HC), cPCR in blood and qPCR in cardiac tissue were used, and the animal that presented negative results in all tests was considered cured. The Y strain was considered resistant to benznidazole, with a mean cure rate (CI) of 4.2%. The essential oil (OE) treatment of C. citratus, Z. officinale and S. aromaticum altered 4/5, 2/5 and 5/5 of the parameters derived from the parasitemia curve, respectively, when compared to the group of non-treated animals. The IC obtained with the OE of C. citratus and Z. officinale was numerically higher but without statistical difference to the group treated with BZ. Treatment with 100 mg / kg dose of S. aromaticum OE provided statistical difference in IC compared to those treated with the standard drug. Article 2 evaluated the efficacy of S. aromaticum OE alone and in combination with benzonidazole in experimentally infected mice with T. cruzi AM14 strain obtained from the vectors. Animals with negative results in the tests of FBE, HC and qPCR in blood and tissue were evaluated after immunosuppression. Infection caused by metacyclic trypomastigotes of insects leads to more intense infectious condition than that caused by metacyclic trypomastigotes of culture. AM14 strain was considered resistant to treatment with BZ (25% cure). OE treatment of S. aromaticum provided an IC of 12.5%, already the association between this essential oil and benzonidazole showed a numerically higher IC result (37.5%) than the treatment with the reference drug. Article 3 evaluated the effect of treatment time on the efficacy of BZ in mice inoculated orally and intraperitoneally with a strain of T. cruzi IV. Inoculated mice were treated with BZ for 20, 40 or 60 consecutive days. The cure rates obtained with treatment times of 20, 40 and 60 days were, respectively, 20.0% (1/5), 75.0% (3/4) and 100.0% (4/4 ) For the IP animals, and 20.0% (1/5), 0.0% (0/5) and 100.0% (5/5) for VO animals, suggesting that the efficacy of BZ is time dependent on T. cruzi IV infection .